Antimicrobials and Antibiotic Resistance Genes in Water Bodies: Pollution, Risk, and Control - Singh, Ashish Kumar; Kaur, Rajinder; Verma, Shashikala; Singh, Samer (Frontiers in Environmental Science, 2022)
The manuscript endeavors to provide a perspective on the role of water bodies in the spread of antimicrobial (antibiotic) resistance (AMR), antimicrobial resistant bacteria (ARB), and antimicrobial resistance genes (ARGs) among pathogens, animals, and humans. We briefly indicate how the AMR problem is globally affecting public health, along with strategies and mechanisms to combat the dissemination of ARB and ARGs. A brief systematic survey of the literature (2015-onwards) for the presence of antimicrobial residues and the occurrence of ARGs and antimicrobial resistant microorganisms in different water bodies/sources indicates the gravity of the situation and suggests their important role in the occurrence and spread of AMR, ARB, and ARGs. The prevalent water treatment methods which tend to reduce ARB and ARGs from water resources are unable to remove them completely, allowing the problem of AMR to continue and spread to organisms of concern. In this opinion article, we attempt to underline the key role of controlling the release/discharge of antimicrobial contaminants in water bodies and their buildup in checking the development and spread of AMR. The reduction in the release of antibiotic residues in the environment, especially water bodies, combined with the development of improved surveillance means and efficacious treatment/removal/decomposition methods could help curb the menace of AMR effectively. We suggest the expansion of the ambit of ‘One Health Approach to AMR crises proposed by the World Bank, 2021 to include the ‘reduction of antimicrobial contamination of the environment’ as the ‘seventh domain’ of activity to effectively achieve its objective.